Urgency of Performance Tiering for Indonesia's Supreme Court: A Constitutional Law Perspective - Nugroho, Agus Digdo; Meliala, Nikko Banta (Jurnal Hukum dan Peradilan, 2024)
The Supreme Court of Indonesia is pivotal as a representative of judicial power. However, evaluations and reports indicate suboptimal performance outcomes, necessitating the implementation of a structured performance tiering framework. This research employs an empirical juridical approach involving surveys, court visits, and focus group discussions, supplemented by a literature review. The study highlights the Supreme Court's need to operationalize its vision of "Realizing Indonesia's Supreme Judicial Body" through clear, measurable performance indicators. Adopting Logical Models, Logical Frameworks, and Critical Success Factors can streamline accountability, enhance judicial efficiency, and ensure alignment across organizational tiers. This paper outlines the steps and benefits of performance tiering in improving Indonesia's judicial system. Performance tiering will become a thinking summary of institutions' functions, use of authority, performance and organization achievements, organization direction, and even paradigm of every process in the Supreme Court and judicial entities under them. The performance tiering of the Supreme Court should ideally adopt the Logical Model, Logical Framework, and Critical Success Factors.